Seed system security assessment: Zimbabwe - International Center for Tropical Agriculture; World Vision; Department of Agricultural Technical and Extension Services, Zimbabwe; International Maize and Wheat Improvement Center; Catholic Relief Services; CARE (International Center for Tropical Agriculture, 2009)
This report presents the results of a Seed System Security Assessment in Zimbabwe, implemented during July 2009.